Building Organizational Agility Through Knowledge Sharing and Organizational Culture in Non-Departmental Government Agencies - Wicaksana, Seta Ariawuri; Reinanda Isfania (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The pace of digital transformation is growing very rapidly in the midst of the current Covid-19 pandemic, resulting in many organizations turning to digital use to be able to compete with other organizations. To be able to keep up with the pace of development, organizations need to transform into agile organizations. One of the things that can be done is to increase organizational agility. To improve an agile organization, employees need to have knowledge that can support it. Knowledge sharing was selected as a variable capable of transforming the organization into an agile organization. In addition, organizational culture has an important role to help and encourage knowledge sharing to create an agile organization. This research is important to do because not many researchers have studied this variable simultaneously so it is hoped that the results of the researchers can be applied in public organizations in Indonesia. This study uses a quantitative approach with data analysis techniques using regression testing with organizational culture as a moderating variable using SPSS and data collection techniques by distributing online questionnaires to 259 participants in non-departmental government agencies. The results show that knowledge sharing has a significant effect on organizational agility, then the value of the influence increases when organizational culture is added. Keywords: digital transformation, organizational agility, knowledge sharing, organizational culture, non-departmental government agencies